Corrosion fatigue behaviors of aluminum alloys for offshore applications - Nguyen, Ngoc Vu (2017)
Pitting corrosion in conjunction with fatigue has been a great concern for structural integrity of aluminium alloys that are being extensively used in offshore applications due to their unique properties, high strength-to-weight ratio compared to other materials. This work investigates the corrosion fatigue behaviors of Aluminum alloys to provide a reliable corrosion fatigue control and further extend the use of aluminum alloys in offshore applications. Firstly, the 3-D morphological damage of pitting corrosion was characterized using confocal microscopy and image processing. Secondly, the effects of crystallographic texture on pitting susceptibility and fatigue performance were studied. Microstructural characteristics of pitting corrosion were examined using Scanning Electron Microscopy and Orientation Imaging Microscopy based analysis technique. Finally, fatigue crack initiation characteristics and crack growth mechanisms of an aluminum alloy when simultaneously subjected to a corrosive environment were investigated.